Skabies di Antara Penyakit Kulit: Studi Prevalensi di Klinik Pratama Soedirman Tahun 2024 - Firinda, Rizma Haidif; Wicaksono, Madya Ardi; Sinensis, Rizki Amelia; Nafiisah, Nafiisah; Kusdaryanto, Wahyu Dwi; Ihtiaringtyas, Suci (Fakultas Kedokteran Universitas Riau, 2025)
Scabies is a skin disease caused by infestation of the parasitic mite Sarcoptes scabiei, which penetrates the skin and reproduces by laying eggs. Although often regarded as a common and non-severe condition, scabies is classified as a neglected skin disease on a global scale. This study aims to determine the prevalence of scabies in relation to the total number of skin diseases diagnosed at the Soedirman Primary Outpatient Clinic. A descriptive research method was employed, utilizing patient medical records from March to September 2024. Data were collected based on ICD-10 diagnostic codes, including both scabies and other dermatological conditions. The results showed that there were 13 recorded cases of scabies (5.05%) out of a total of 257 diagnosed skin diseases. This prevalence closely aligns with the national prevalence of scabies in Indonesia. Variations in prevalence may be influenced by social and environmental factors, with higher transmission rates occurring in densely populated areas and among individuals with frequent close contact. Preventive measures include health education, personal hygiene, and improved environmental sanitation.